GENOTYPIC AND PHENOTYPIC VARIATION AND SELECTION INDEX IN F4 OF TWO ROWBARLEY(Hordeum vulgare L. - Raad Ahmed Hammed; Mohammad Y.H. AL-Fahady; Wiam Y. Rasheed (Mesopotamia Journal of Agriculture)
F4 population derived from diallel crosses between five two row varieties (Local Aswad, Tuwwtha , Arta , Zanbaka and Gezira 2) to study genotypic and phenotypic variances , heritability , genetic advance and study genotypic and phenotypic correlations of number of days to flowering and maturity , plant height ,number of spikes and grains per spike, 100 grains weight and grain and biological yield and determine better selection index which gave highest genetic advance for grain yield. Significant differences were observed between genotypes for all studied characters. Genotypic and phenotypic variances values were low for number of days to flowering and maturity, number of grains per spike, 1000 grains weight and high for plant height, no of spikes and grain and biological yield. High broad sense heritability values were obtained for number of days to maturity, plant height, number of grains per spike and 100 grain. Grain yield correlated genetically negatively and highly significant with number of days to flowering and 100 grain weight and positively with plant height and number of spikes and grains per spike and biological yield. The selection index including number of grains per spike was the best one which gave high relative efficiency on which we could depend to estimate the values of selection index for the studied genotypes.